Preparation method of submicron nano ceramic film on metal surface

By using pulsed laser scanning technology to form and optimize carbon-nitrogen nanoceramic films on metal surfaces, the problem of difficulty in building dense nanoceramic films in the prior art is solved, and high wear resistance and long-term use of metal surfaces are achieved.

CN119465146AActive Publication Date: 2025-02-18MATERIAL INST OF CHINA ACADEMY OF ENG PHYSICS
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411664891.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently and conveniently build a dense submicron-scale carbon-nitrided nanoceramic film on the metal titanium surface, resulting in surface wear problems during use of titanium joints, affecting their long-term useability.

Method used

By uniformly coating carbon powder on the metal surface and using pulsed laser scanning technology in a nitrogen atmosphere, the first carbon-nitrogen nanoceramic film is formed, and the second coating and laser scanning are performed on its surface, the formed carbon-nitrogen nanometers are optimized. Ceramic film.

Benefits of technology

It has achieved the construction of dense nanoceramic films with high load-bearing capacity, high hardness, high bonding strength, good wetting and good finish on the metal surface, which significantly reduces the friction coefficient of the metal surface and improves its wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465146A_ABST
    Figure CN119465146A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a submicron nano ceramic film on a metal surface, and belongs to the field of film preparation, the surface of a metal base material is coated with powder, a large amount of plasma containing carbon, nitrogen and metal elements is instantly generated on the surface of the metal base material under the action of pulse laser in a nitrogen atmosphere, and the metal surface is coated with the powder. The plasma is back-flushed to the surface of the metal base material; and due to the extremely cold effect of the surface of the substrate, the effect of refining cladding surface layer grains is achieved, and finally the compact submicron carbonitride nano ceramic film is formed on the surface of the metal substrate. The surface film has high bearing capacity, high hardness, high bonding strength, good wettability and good smoothness while the necessary mechanical properties of a metal component are not affected, the friction coefficient of the metal surface can be remarkably reduced, and the wear resistance of the metal surface is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of film preparation, and in particular to a method for preparing a submicron nano ceramic film on a metal surface. Background Art

[0002] The surface wear resistance of precision metal devices with high added value will greatly affect their reliability in engineering applications, such as precision bearings (steel) in aerospace or artificial joints and bones (titanium) in the medical field. Among them, metal titanium, as an important structural metal, has been widely used in aerospace, medical and health, chemical machinery, sports goods and other fields since the 1950s because of its good corrosion resistance, low density, high specific strength, low thermal conductivity, non-toxic and non-magnetic, good biocompatibility, and easy surface modification. For example, because titanium is close to human bones, it has good biocompatibility and no toxic side effects on human tissues. Bones, joints, instruments, etc. made of metal titanium have good transplantation effects in the human body. In order to ensure that titanium structural parts meet the performance requirements in specific occasions, it is usually necessary to prepare titanium alloys with corresponding properties. However, in the use of titanium components (titanium and titanium alloys), it is necessary not only to consider mechanical properties (high strength, high toughness, etc.), but also to consider its surface physical and chemical properties in the environment, such as wear resistance. Titanium joints have surface wear problems during use, and the wear debris can cause aseptic loosening, which eventually leads to failure of replacement joints. Therefore, how to prepare a dense nano-ceramic film with high load-bearing capacity, high hardness, high bonding strength, good wettability and good finish on the surface without affecting the necessary mechanical properties of titanium joints is a difficulty in further improving the long-term usability of artificial joints.

[0003] Based on this, the development of efficient and universal metal surface nano-ceramic film preparation technology will greatly promote the application of high-value-added components such as precision bearings or artificial bones and joints in aerospace or medical and health. At present, the commonly used coating methods include sputtering deposition, vacuum evaporation, ion implantation, electrochemical deposition and laser cladding. The characteristics of each technology are as follows:

[0004] Sputtering deposition technology uses the process of electrons accelerating to fly to the substrate under the action of an electric field to collide with argon atoms, ionizing a large number of argon ions and electrons, and the electrons fly to the substrate. Argon ions are accelerated to bombard the target material under the action of the electric field, sputtering a large number of target atoms, and neutral target atoms (or molecules) are deposited on the substrate to form a film. The characteristics of this technology are high film formation rate, low substrate temperature, good film adhesion, and large-area coating. By changing the process parameters and target composition, the composition and properties of the film can be flexibly controlled. The prepared alloy film has uniform composition, good density and performance, high deposition rate, good bonding strength with the substrate, and nitride film can be obtained by introducing reaction gas. However, this technology has low target utilization and high cost. In addition, there is a relatively obvious stratification between the prepared alloy film and the substrate, and the bonding strength needs to be further considered, which limits its application to a certain extent.

[0005] The equipment used in vacuum evaporation technology is relatively simple and easy to operate; the prepared thin film has high purity and fast film formation speed; the thin film growth mechanism is simple and easy to control and simulate. However, it is not easy to obtain a thin film with a crystal structure; the deposited film has poor adhesion to the substrate.

[0006] The ion implantation method has good film adhesion, high film density, high deposition rate, and is conducive to the formation of composite films, which can be plated with a variety of materials. However, the defect density in the film is higher, the transition zone between the film and the substrate is wider, and the residual gas content in the film is higher.

[0007] Electrochemically deposited thin films can be uniformly deposited on substrates with complex structures; by controlling process parameters, the thickness and composition of the film can be easily controlled; the process is simple, easy to operate, and economical. However, it is difficult to prepare ideal and complex composite films; parameters such as current and voltage are prone to fluctuations, resulting in poor uniformity of the deposited layer.

[0008] Laser cladding technology can quickly achieve surface alloying on metal surfaces, but the thickness of the modified layer formed by this technology is about hundreds of microns, and the surface morphology and roughness after treatment vary greatly, making it difficult to be widely used in precision metal devices with high surface finish requirements.

[0009] In summary, it is difficult to efficiently and conveniently construct dense submicron carbonitride nanoceramic films on the surface of metal titanium using coating technologies such as sputtering deposition, vacuum evaporation, ion implantation, electrochemical deposition and laser cladding. Summary of the invention

[0010] The purpose of the present invention is to provide an efficient and reliable technology for the preparation of submicron nano-ceramic films on metal surfaces by constructing submicron nano-ceramic films on metal surfaces. While not affecting the mechanical properties of the metal substrate and not degrading the surface finish of the substrate, the metal surface is given excellent friction reduction and wear resistance. For titanium metal, its lubrication and wear resistance and biocompatibility can be improved; for steel devices such as precision bearings, its surface wear resistance can be enhanced, expanding the engineering application range of metal materials.

[0011] The objective of the present invention is achieved through the following technical solutions:

[0012] A method for preparing a submicron-scale nano-ceramic film on a metal surface is provided, comprising the following steps:

[0013] S1. evenly coating carbon powder on the surface of the metal substrate to be modified;

[0014] S2, in a nitrogen atmosphere, scanning the surface of the metal substrate by a first pulse laser to form a first carbon-nitrogen nano-ceramic film on the surface of the metal substrate;

[0015] S3, coating the carbon powder in step S1 on the first carbon nitride nano-ceramic film, scanning the first carbon nitride nano-ceramic film with a second pulse laser, and forming an optimized carbon nitride nano-ceramic film on the surface of the metal substrate.

[0016] Preferably, the step S1 specifically includes:

[0017] A small amount of solvent is brushed on the surface of the metal substrate to be modified, and then the surface is wiped dry with a non-woven fabric; then, a certain amount of carbon material is weighed and rubbed on the surface of the metal substrate.

[0018] Preferably, the coating amount of the carbon material is 1 mg / cm 2 ~15mg / cm 2 .

[0019] Preferably, the solvent includes but is not limited to paraffin, glycerol or edible oil; and the carbon material is graphene or carbon nanotubes.

[0020] Preferably, the metal substrate includes but is not limited to metal titanium, steel, uranium, and copper.

[0021] Preferably, the nitrogen atmosphere is 1 to 3 atmospheres.

[0022] Preferably, the nitrogen atmosphere is replaced by a solid material containing nitrogen, and the solid material containing nitrogen is loaded on the surface of the metal substrate by coating before the first pulse laser scanning.

[0023] Preferably, the solid material containing nitrogen element includes but is not limited to boron nitride and silicon nitride.

[0024] Preferably, the first pulse laser scanning parameters include:

[0025] Scanning step: 0.4-2.5 mm, scanning speed: 500-10000 mm / s, pulse laser energy: 5-100 W, energy density: 5-20 J / cm 2 .

[0026] Preferably, the second pulse laser scanning parameters include:

[0027] Scanning step: 0.4~1.0mm, scanning speed: 1000~5000mm / s, pulse laser energy: 5~30W, overlap rate: 30%~90%, energy density: 0.5~2J / cm 2 .

[0028] It should be further explained that the technical features corresponding to the above options can be combined or replaced with each other to form a new technical solution if there is no conflict.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) Almost no effect on the mechanical properties of the metal substrate: The present invention utilizes the rapid melting extreme cold effect produced by the pulsed laser on the metal surface to instantly generate a large amount of plasma, and incorporates non-metallic elements such as carbon and nitrogen into the metal surface, thereby refining the grains and forming a nano-ceramic film with a submicron thickness that is metallurgically bonded to the metal surface. Compared with other surface modification technologies, the present invention has a negligible effect on the mechanical properties of the substrate itself (the thickness of the modified layer formed by traditional continuous laser cladding and thermal spraying technologies is hundreds of microns or millimeters, which has a greater impact on the mechanical properties and surface micromorphology of thinner metal substrates). Finally, the laser energy density and other parameters are adjusted, and the powder-coated metal surface is scanned again to optimize the prepared nano-ceramic film, so that the surface film has high load-bearing capacity, high hardness, high bonding strength and good wettability and maintains good finish, which can significantly reduce the friction coefficient of the metal surface and improve its wear resistance.

[0031] (2) The carbonitride nano-ceramic film is dense and has strong bonding with the substrate: pulsed laser can achieve rapid melting and extreme cooling on the metal surface. The surface of the ceramic film is dense and continuous. During the extreme cooling process, the grains are refined to the nanoscale. The ceramic film and the substrate are metallurgically bonded and there is no boundary layer (the modified layer constructed on the metal surface by magnetron sputtering, pulsed laser deposition, vacuum evaporation and other technologies has an obvious boundary layer with the substrate, and the density of the modified layer is poor. It is usually necessary to increase the thickness of the modified layer to improve the density).

[0032] (3) The composition of the ceramic film is simple and controllable: By adjusting the amount and type of powder coating on the surface of the modified layer or the nitrogen atmosphere, the composition of the ceramic film can be controlled and ceramic films with different element ratios can be designed. (Techniques such as electrochemical deposition and ion implantation have relatively strict requirements on the composition of the added elements).

[0033] (4) Simple and efficient, no need for high pressure and high temperature: The entire nano-ceramic film preparation process can be carried out at room temperature and 1 to 3 atmospheres of pressure, without the need for high temperature and high pressure. (Ion implantation technology usually requires a temperature of more than 300°C). BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 A flow chart of a method for preparing a submicron nano-ceramic film on a metal surface according to an embodiment of the present invention;

[0035] Figure 2 A practical flow chart of a method for preparing a nano-ceramic film according to an embodiment of the present invention;

[0036] Figure 3 The figure shows the wear morphology and friction coefficient change of the metal substrate before and after surface modification according to the embodiment of the present invention. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present application described and shown in the accompanying drawings can be arranged and designed in various configurations. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0038] It should be noted that the defects existing in the solutions in the above-mentioned prior art are the results obtained by the inventor after practice and careful research. Therefore, the discovery process of the above-mentioned problems and the solutions proposed in the embodiments of the present application for the above-mentioned problems below should all be the contributions made by the inventor to the present application in the process of invention and creation, and should not be understood as technical contents known to technical personnel in this field.

[0039] In view of the technical problems pointed out in the background technology, the embodiments provided by the present invention are as follows:

[0040] Example 1

[0041] Reference Figure 1 In an exemplary embodiment, a method for preparing a submicron nano-ceramic film on a metal surface is provided, comprising the following steps:

[0042] S1. evenly coating carbon powder on the surface of the metal substrate to be modified;

[0043] S2, in a nitrogen atmosphere, scanning the surface of the metal substrate by a first pulse laser to form a first carbon-nitrogen nano-ceramic film on the surface of the metal substrate;

[0044] S3, coating the carbon powder in step S1 on the first carbon nitride nano-ceramic film, scanning the first carbon nitride nano-ceramic film with a second pulse laser, and forming an optimized carbon nitride nano-ceramic film on the surface of the metal substrate.

[0045] The principle of this method is:

[0046] When the pulse laser acts on the surface of the metal substrate coated with carbon powder, a rapid melting and extreme cold effect is generated. The material on the surface of the metal substrate (micron-level depth) will absorb a large amount of energy within nanoseconds and instantly generate a large amount of plasma. At this time, the surface of the metal substrate is in a rapid melting state. Compared with the high-temperature plasma, the surface temperature of the metal substrate and the ambient temperature of the atmosphere are at room temperature (tens of degrees Celsius), and it is a cold body. When the plasma contacts the surface of the metal substrate, it will be instantly cooled and solidified on the surface of the metal substrate, and non-metallic elements such as carbon and nitrogen will be incorporated into the metal surface, refining the grains to form a submicron-thick nano-ceramic film metallurgically bonded to the surface of the metal substrate. Finally, the parameters of the second pulse laser scan (laser energy density, etc.) are adjusted, and the surface of the powder-coated metal substrate is scanned again to achieve the optimization of the prepared nano-ceramic film.

[0047] like Figure 2 As shown, powder coating is performed in step S1. Specifically, a small amount of solvent (such as paraffin, glycerin, edible oil, etc.) is first brushed on the surface of the metal substrate to be modified, and then the surface is wiped dry with a non-woven fabric. Then, a certain amount of industrial graphite is weighed and rubbed on the metal surface, and the coating amount is controlled at 1 mg / cm 2 ~15mg / cm 2 The main purpose of brushing the surface of the metal substrate with solvent is to facilitate the dispersion and adhesion of the powder on the surface of the metal substrate. The specific implementation process depends on the surface roughness of the metal substrate. For substrates with rough surfaces, powder coating can also be directly performed. The coated material is not limited to carbon powder, and the coating amount is adaptively adjusted according to the material and surface state of the metal substrate and the type of material to be coated.

[0048] In step S2, a carbon-nitrogen nano-ceramic film is prepared. First, a metal substrate uniformly coated with carbon powder is placed on an operating table under a nitrogen atmosphere (1 to 3 atmospheres); then the pulse laser scanning step length (0.4 to 2.5 mm), scanning speed (500 to 10000 mm / s), pulse laser energy (5 to 100 W), and energy density (5 to 20 J / cm 2) and other parameters to form a carbon-nitrogen nano-ceramic film on the surface of a metal substrate. The sources of nitrogen and other non-metallic elements include, but are not limited to, nitrogen gas, and may also be other solid materials containing nitrogen, such as boron nitride, silicon nitride and other materials, which may also be loaded on the surface of a metal substrate by coating before the laser is applied, to achieve the preparation of nano-ceramic films containing other non-metallic elements.

[0049] In step S3, the carbon nitride nano-ceramic film is optimized. Specifically, steps S1 and S2 are repeated, and the powder prepared in step S1 is coated on the surface of the metal substrate treated in step S2, and the pulse laser scanning step length (0.4-1.0 mm), scanning speed (1000-5000 mm / s), pulse laser energy (5-30 W), overlap rate (30%-90%), and laser energy density is adjusted to 0.5-2 J / cm 2 , optimizing the first carbonitride nanoceramic film prepared in step S2. The friction coefficient of the metal surface can be significantly reduced, and its wear resistance can be improved. It should be noted that in practical applications, the first carbonitride nanoceramic film can be optimized once or multiple times according to actual conditions until the friction coefficient of the metal surface is reduced to the target requirement.

[0050] Example 2

[0051] Based on the inventive concept of Example 1, this example provides a method for preparing a submicron nano-ceramic film on a titanium metal surface. The method comprises:

[0052] Step 1 (powder coating): First, brush a small amount of paraffin wax on the surface of the titanium metal, and then wipe the surface dry with a non-woven fabric. Then, weigh a certain amount of industrial graphite and apply it on the metal surface. The coating amount is controlled at 15mg / cm 2 ;

[0053] Step 2 (preparation of nano-ceramic film): First, in a nitrogen atmosphere (1 atmosphere), a metal titanium substrate uniformly coated with carbon powder was placed on an operating table; then the pulse laser scanning step length (0.4 mm), scanning speed (10000 mm / s), pulse laser energy (100 W), energy density (20 J / cm 2 ) and other parameters, a carbon-nitrogen nano-ceramic film is prepared on the surface of metal titanium;

[0054] Step 3 (Nano-ceramic film friction reduction optimization): Repeat steps 1 and 2, and apply the powder prepared in step 1 to the titanium surface treated in step 2 (the coating amount is 15 mg / cm 2 ), control the pulse laser scanning step length (1.0mm), scanning speed (1000mm / s), pulse laser energy (30W), overlap rate (90%), and adjust the laser energy density to 2J / cm 2, optimize the carbonitride nanoceramic film prepared in step two.

[0055] The data of the changes in the surface morphology and friction coefficient of the modified titanium surface after the wear test in this embodiment are as follows:

[0056] Figure 3 The wear morphology and friction coefficient change diagram of titanium metal before and after surface modification (reciprocating wear, the grinding pair is Si3N4 ball, φ = 6mm). Figure 3 As shown in (a) and 3(d), the surface of unmodified titanium (Ti) will suffer severe wear at the initial stage of wear under a load of 1N, and the friction coefficient fluctuates around 0.5. After the wear is over, the wear scar width reaches 900μm; Figure 3 As shown in (b) and 3(d), after the carbonitride nano-ceramic film (TiN / C) is constructed on the surface of metal titanium, its surface wear resistance is improved to a certain extent. It has a low friction coefficient (0.15) at the initial stage of wear. However, as the wear progresses, its friction coefficient gradually increases. When the wear distance reaches 6m, its friction coefficient rises to above 0.6. This shows that the carbonitride ceramic layer on the surface has been worn, and the abrasive particles generated have aggravated the abrasive wear of the surface, resulting in its friction coefficient being greater than that of the unmodified metal titanium. The color of the wear scar area is obviously different from that of the unworn area, and the wear scar width is 500μm. After the carbonitride ceramic layer is optimized (TiN / CL), as shown in Figure 3 As shown in Figures 3(c) and 3(d), during the entire friction process, the optimized ceramic film has a stable and extremely low friction coefficient (0.15) before the friction distance of 35 m. After the 50 m wear test, by observing the wear marks, it can be found that the wear mark area still retains good corrugated marks after laser modification, and the color is similar to that of the unworn area. This shows that the optimized nano-ceramic layer has stable wear resistance, and the wear resistance is improved by about 600% compared with before optimization.

[0057] Example 3

[0058] Based on the inventive concept of Example 1, a method for preparing a submicron nano-ceramic film on a steel surface is provided. The method comprises:

[0059] Step 1 (powder coating): First, brush a small amount of paraffin wax on the surface of 45# steel, and then wipe the surface dry with a non-woven cloth. Then, weigh a certain amount of industrial graphite and apply it on the metal surface. The coating amount is controlled at 1mg / cm 2 ;

[0060] Step 2 (preparation of nano-ceramic film): First, in a nitrogen atmosphere (2 atmospheres), place a metal substrate uniformly coated with carbon powder on an operating table; then control the pulse laser scanning step length (2.5 mm), scanning speed (500 mm / s), pulse laser energy (5 W), energy density (5 J / cm 2 ) and other parameters, carbon nitride nano-ceramic film was prepared on the surface of 45 steel;

[0061] Step 3 (nano-ceramic film optimization): Repeat steps 1 and 2, and apply the powder prepared in step 1 to the surface of 45 steel treated in step 2 (the coating amount is 1 mg / cm 2 ), control the pulse laser scanning step length (0.4mm), scanning speed (5000mm / s), pulse laser energy (5W), overlap rate (30%), and adjust the laser energy density to 0.5J / cm 2 , optimize the carbonitride nanoceramic film prepared in step two.

[0062] The data on the changes in surface morphology and friction coefficient of the modified steel surface after the wear test in this embodiment are similar to those in Example 2, and are not described in detail here.

[0063] Example 4

[0064] Based on the inventive concept of Example 1, another method for preparing a submicron nano-ceramic film on a titanium metal surface is provided. The method comprises:

[0065] Step 1 (Carbon powder coating preparation): First, brush a small amount of paraffin wax on the titanium surface, and then wipe the surface dry with a non-woven fabric. Then, weigh a certain amount of graphene and apply it on the metal surface. The coating amount is controlled at 8 mg / cm 2 ;

[0066] Step 2 (preparation of submicron nano-ceramic films): First, in a nitrogen atmosphere (3 atmospheres), place a metal substrate uniformly coated with carbon powder on an operating table; then control the pulse laser scanning step length (1.2 mm), scanning speed (5000 mm / s), pulse laser energy (60 W), energy density (15 J / cm 2 ) and other parameters, a carbon-nitrogen nano-ceramic film is prepared on the surface of metal titanium;

[0067] Step 3 (nano-ceramic film optimization): Repeat steps 1 and 2, and coat the powder prepared in step 1 on the titanium surface treated in step 2 (coating amount is 5 mg / cm 2 ), control the pulse laser scanning step length (0.8mm), scanning speed (2000mm / s), pulse laser energy (18W), overlap rate (50%), and adjust the laser energy density to 1J / cm 2, optimize the carbonitride nanoceramic film prepared in step two.

[0068] The data on the changes in surface morphology and friction coefficient of the modified titanium surface after the wear test in this embodiment are similar to those in Example 2, and are not described in detail here.

[0069] In summary, the present invention constructs a submicron-thick carbonitride nano-ceramic film with an extremely low friction coefficient and metallurgically bonded to the substrate on the metal surface by successively performing powder coating, laser rapid melting and extreme cold cladding, and laser surface friction reduction optimization on the metal surface. This is a simple and efficient technology for preparing nano-ceramic films on metal surfaces and has great potential for engineering applications.

[0070] The above specific implementation methods are detailed descriptions of the present invention. It cannot be determined that the specific implementation methods of the present invention are limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions and substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.

Claims

1. A method for preparing a submicron nano-ceramic film on a metal surface, characterized in that: The following steps are involved: S1. evenly coating carbon powder on the surface of the metal substrate to be modified; S2, in a nitrogen atmosphere, scanning the surface of the metal substrate by a first pulse laser to form a first carbon-nitrogen nano-ceramic film on the surface of the metal substrate; S3, coating the carbon powder in step S1 on the first carbon nitride nano-ceramic film, scanning the first carbon nitride nano-ceramic film with a second pulse laser, and forming an optimized carbon nitride nano-ceramic film on the surface of the metal substrate.

2. The method for preparing a submicron nano-ceramic film on a metal surface according to claim 1, characterized in that: The step S1 specifically includes: A small amount of solvent is brushed on the surface of the metal substrate to be modified, and then the surface is wiped dry with a non-woven fabric; then, a certain amount of carbon material is weighed and rubbed on the surface of the metal substrate.

3. The method for preparing a submicron nano-ceramic film on a metal surface according to claim 2, characterized in that: The coating amount of the carbon material is 1 mg / cm 2 ~15mg / cm 2 .

4. The method for preparing a submicron nano-ceramic film on a metal surface according to claim 2, characterized in that: The solvent includes but is not limited to paraffin, glycerol or edible oil; the carbon material is graphene or carbon nanotubes.

5. The method for preparing a submicron nano-ceramic film on a metal surface according to claim 1, characterized in that: The metal substrate includes but is not limited to metal titanium, steel, uranium, and copper.

6. The method for preparing a submicron nano-ceramic film on a metal surface according to claim 1, characterized in that: The nitrogen atmosphere has a pressure of 1 to 3 atmospheres.

7. The method for preparing a submicron nano-ceramic film on a metal surface according to claim 1, characterized in that: The nitrogen atmosphere is replaced by a solid material containing nitrogen, and the solid material containing nitrogen is loaded on the surface of the metal substrate by coating before the first pulse laser scanning.

8. The method for preparing a submicron nano-ceramic film on a metal surface according to claim 7, characterized in that: The nitrogen-containing solid material includes but is not limited to boron nitride and silicon nitride.

9. The method for preparing a submicron nano-ceramic film on a metal surface according to claim 1, characterized in that: The first pulse laser scanning parameters include: Scanning step: 0.4-2.5 mm, scanning speed: 500-10000 mm / s, pulse laser energy: 5-100 W, energy density: 5-20 J / cm 2 .

10. The method for preparing a submicron nano-ceramic film on a metal surface according to claim 1, characterized in that: The second pulse laser scanning parameters include: Scanning step: 0.4~1.0mm, scanning speed: 1000~5000mm / s, pulse laser energy: 5~30W, overlap rate: 30%~90%, energy density: 0.5~2J / cm 2 .

Citation Information

Patent Citations

  • Titanium carbide metal ceramic powder and method for laser cladding of powder

    CN102962447A

  • Powder for high-entropy alloy-based composite material modified layer prepared on ferrous alloy surface

    CN104651828A

  • Preparation method for alloy ceramic film, mobile terminal shell and mobile terminal

    CN105624671A

  • Preparation method of wear-resistant metal-multi-element ceramic composite modified coating on surface of titanium alloy

    CN113667974A

  • Method for preparing aluminum alloy super-hydrophobic surface through flat-top laser peening

    CN114985938A